Akibat Hukum dan Pelaksanaan Tanggung Jawab Bagi Notaris/PPAT Yang Melakukan Tindak Pidana Kecurangan Dalam Pembuatan Sebuah Akta (Jurnal Begawan Hukum (JBH), 2024)
The authority of the notary in carrying out the duties as well as the office of a notary. In article 1, paragraph (1) of Act No. 30 of 2004 on the Office of Notaries, notaries are public officials authorized to make authentic acts and other authorities as referred to in this Act. One of the notary's powers is to make authentic acts. The acts made by the notary, for example, the appointment of a limited company (PT), changes and public records of shareholders, founding of foundations, establishment of materials of other enterprises, authority to sell, lease agreement, sale agreements, declaration of inheritance rights, wills, establishing of CV including its modifications, recognition of debt, credit agreements and granting of liability, cooperation agreements, employment contracts, all forms of agreements not excluded to other officials, therefore the act relating to the agreement of absolute cooperation is authority by the Notary to make such an authentic act. This is what can be investigated about the notary's authority in authentication. This research uses the method of normative legal research, normative law research is an approach that is applied to discussing research issues through the statue approach, the analytical and conceptual approach and the comparative approach. (Comparative Approach). From the results of the research can be drawn the conclusion that a particular act is judged as a criminal act based on the result of a normative consideration of several judges decisions.